Trajetórias acadêmicas de estudantes negros e negras cotistas do curso de Pedagogia da Universidade Federal do Maranhão - Campus Imperatriz - SOUSA, Lizandra Sodré (2022)
This dissertative paper, entitled “An anti-racist approach to the School Psychology at the Federal university of Maranhão- Campus Imperatiz”, is the resulto f the concerns arising while working with the School Psychology in the College Education and the need and urgency for understanding of how the Ethnic-Racial Ralations develop themselves in this context. Our paper is justified by the need for the university to be a fruitful environment for the development of anti-racist institutional practices considering the presence of black students in this educational space. The guiding questions that guided the study were: How my identity formation contribute to the study of ethnic-racial relations in Colleg Education? How are the academic paths of male and female students that entered through raciais quotas in the couse of Psychology in the Federal University of Maranhão – Imperatriz Campus? How did the process of racial self identification of quota students take place? How are racial relations developed in the Pedagogy course at the Federal University of Maranhão? From this, we outline the following objectives: (a) describe how does my identity formation contributes to the study os the ethic-racial relations in the College Education; (b) analize the academic tragectories of male and female students entering through racial quotas in the course of Pedagogy at the Federal University of Maranhão – Imperatriz Campus; (c) investigate how the process of racial identification of black and female quota students took place and (d) understand how racial relations develop in the Pedagogy course at UFMA. The paper is anchored in authors who approach the theme of racial relations in Brazil, quota policies and School Psychology regarding racial issues, among which we can mention: Nilma Lino Gomes (2001, 2005, 2006, 2007 , 2017, 2019, 2021), Kabengele Munanga (2004, 2006, 2016, 2020), Antonio Sérgio Alfredo Guimarães (1999, 2003), José Jorge de Carvalho (2006), Lia Vainer Schucman (2010, 2014, 2017, 2018) , Claisy Marinho-Araújo (2014, 2015, 2016), Adrielle de Matos Borges Teixeira, (2018, 2019) and Maria Virginia Machado Dazzani (2018, 2019). The research has an essentially qualitative character under the epistemological contribution of the Historical-Cultural Psychology of human development. The methodological path was developed from institutional mapping through documentary sources and interviews. The interviews were carried out with the psychology professional on the campus and with quota students from the Pedagogy course who entered the university in the “black and brown” category. This investigation has professional, social and academic relevance, because from it we hope to build subsidies for the development of anti-racist institutional policies and practices and, consequently, contribute to the permanence of quota students in Higher Education with dignity. The information was analyzed based on the concept of zones of meaning, constructed from the participants' speeches through a critical interpretation of the phenomena presented in the research process. Among other things, the results showed that the psychological actions developed are aimed at all those who have difficulties in staying in Higher Education, with no specific actions aimed at the black public at the university; the identity formation of the student body is strongly influenced by the family context; the university presents itself as a fruitful space for the strengthening of racial identities; the UFMA Pedagogy course has been committed to training pedagogues in a democratic perspective; financial aid and scholarships prove to be an essential factor for the dignified permanence of quota students. Finally, as research developments, we suggest propositions for collective and institutional actions in order to enable better conditions of permanence for black students and quota holders at UFMA.